The Effect of Systematic Learning on Improving Volleyball Underhand Passing Skills Among Extracurricular Students at SDN Cisalak 2 - Ridwan Maulana Sidik; Entan Saptani; Anggi Setia Lengkana (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2026)
This study aimed to analyze the effect of systematic learning on improving volleyball underhand passing skills among extracurricular students at SDN Cisalak 2. The study employed a quasi-experimental method using a pretest–posttest control group design. The sample consisted of 20 students selected through total sampling and divided equally into an experimental group and a control group. The experimental group received systematic learning treatment, while the control group was taught using conventional learning methods. The instrument used was the AAHPER underhand passing skill test. Data were analyzed using descriptive statistics, normality tests, paired sample t-tests, and independent sample t-tests. The findings revealed that both groups experienced improvement; however, the experimental group demonstrated significantly higher improvement than the control group. The hypothesis test showed a significance value of 0.000 (p < 0.05), indicating a significant effect of systematic learning on students’ underhand passing skills. In addition, the effect size analysis produced a Cohen’s d value of 3.07, categorized as a very large effect. Therefore, systematic learning can be considered an effective instructional approach for improving basic volleyball techniques among elementary school students.